EKSPLORASI KECURANGAN KEUANGAN PT. ASABRI (PERSERO) MELALUI PENDEKATAN CASH FLOW SHENANIGANS - Natalis Christian; Arlina Arlina; Julie Tryany; Vera Laurence Liang; Yohanis Rerung (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2024)
The phenomenon of fraud in financial reports has become a global issue that affects market integrity and investor confidence. This study aims to identify fraudulent practices in PT Asabri (Persero)'s cash flow reports with a focus on cash flow shenanigans techniques. The research method uses forensic analysis and investigative audits of Asabri's financial reports from 2012 to 2017. The research results show indications of cash flow manipulation through the cash flow shenanigans no. 1, 2, and 3. This study highlights the importance of understanding and monitoring transparent and accurate accounting practices in public companies. Irregularities in financial statements not only harm investors, but can also create overall market instability. This study also highlights the need for tighter supervision and regulation of public financial reporting, especially in the state-owned pension and insurance sectors. Overall, the findings of this article can not only increase awareness of the risks of fraud in financial reporting, but can also serve as a guide for regulators and practitioners in efforts to prevent and detect similar practices in the future.